DEVELOPMENT OF BEJAMI (BELAJAR EKONOMI) LEARNING MEDIA BASED ON ANDROID APPLICATIONS AS AN INNOVATION IN SOCIAL STUDIES LEARNING IN GRADE V OF ELEMENTARY SCHOOL - Wita Sari; Rana Gustian Nugraha; Enjang Yusup Ali (Jurnal Cakrawala Pendas, 2025)
The purpose of this study was to identify the extent to which the results of the development of BEJAMI (Belajar Ekonomi) learning media on economic activity material in grade V of elementary school. BEJAMI learning media is an android application that has several features including learning materials, learning videos, educational games and learning reflections. The research method used in this material is Research and Development (RnD) and uses the ADDIE model which includes 5 stages, namely analysis, design, development, implementation, and evaluation. The results of this study are that BEJAMI learning media is suitable for use in the learning process by obtaining an average media validation result of 91.5%, an average material validation of 94%, and an average language validation result of 98%. Media trials were carried out in three stages, namely individual trials obtaining results of 92.8%, in small groups of 91.32%, and in large groups of 89.32%. Thus, BEJAMI learning media is considered very good as a learning media used in social studies subjects on economic activity material in everyday life in grade V of elementary school.